تأثير ممارسات إدارة المواهب على أداء العاملين: دراسة تطبيقية على العاملين بالهيئات الاتحادية في دولة الإمارات العربية المتحدة - أبو نمر، مي إبراهيم محمد; الشوادفي، محمد غمري; جوده، يسري السيد يوسف Jawdah, Yusri Alsayed Yousuf (جامعة بنها - كلية التجارة, 2019)
هدفت هذه الدارسة إلى التعرف على العلاقة بين ممارسات إدارة المواهب على أداء الموظفين العاملين في وزارة التربية والتعليم كهيئة اتحادية في دولة الأمارات العربية المتحدة. استخدمت الباحثة في هذه الدراسة المنهج الوصفي التحليلي، والاستبانة كأداة لجمع البيانات وكانت مجالات محورها مقسمة بين محورين رئيسين هما ممارسات إدارة المواهب (استقطاب وجذب الموهبة، اختيار الموهبة، تحفيز وتطوير الموهبة، الاحتفاظ بالموهبة، تخطيط التعاقب والاستبدال) كمتغير مستقل وأداء العاملين (الانضباط، إنجاز المهام، العلاقة مع المسؤولين بالعمل، العلاقة مع زملاء العمل) كمتغير تابع. قامت الباحثة بتوزيع (٣٣٤) استمارة استقصاء على الموظفين الإداريين العاملين في الوزارة، وتبين بعد مراجعة الاستمارات أن هناك (64) استمارة غير صالحة للتحليل الإحصائي، وبهذا تكون عينة الدراسة (٢٧٠) من العاملين بالمستويات الإدارية الثلاثة (الإدارة العليا، الإدارة الوسطى، الإدارة الإشرافية) من وزارة التربية والتعليم، وبذلك بلغ معدل الاستجابة الكلي (80.8) بالنسبة لعينة الدراسة. وقد أظهرت نتائج الدراسة نتائج أهمها: أن مستوى تطبيق ممارسات إدارة المواهب في وزارة التربية والتعليم جاء مرتفعا، وكما كان ترتيب هذه الممارسات كأقوى المؤثرات من وجهة نظر العاملين بالوزارة على النحو التالي استقطاب وجذب الموهبة، يليه اختيار الموهبة، ثم الاحتفاظ بالموهبة، يليه تحفيز وتطوير الموهبة، ثم تخطيط التعاقب والاستبدال، مما يعكس اهتمام الوزارة باستقطاب وجذب الموهبة ثم اختيارها والاحتفاظ بها والعمل على تحفيزها وتطويرها وتخطيط المسار الوظيفي لها. وقدمت الدراسة جملة من التوصيات منها: تصميم سياسات واستراتيجيات حديثة وثقافات تنظيمية لتطبيق ممارسات إدارة المواهب في المنظمات الحكومية مع الاستفادة من التجارب والممارسات العالمية الناجحة في هذا المجال.
The purpose of the study was to examine the effect of talent management practices on employee performance at the Ministry of Education as a federal entity in the United Arab Emirates. To achieve the goal of the study the researcher used the descriptive analytical method. The two main variables are: Talent Management practices as Independent variable with the following attributes (attracting and recruitment talent, talent selection, motivating and developing talent, retention talent, and succession planning and replacement). The second variable is employee performance as dependent variable that has the following attributes (Discipline, achievement of tasks, relationship with employers, relationship with coworkers). The study adopted a descriptive survey research design. The researcher distributed the survey on (334) employees working in the ministry. After reviewing the survey respondents, it was found that (64) respondents are not valid. From that the sample size on (270) respondents among the three levels of management (low-level management, middle-level management, and top-level management) at the Ministry of Education, tied the total response rate (80.8%) of the study sample. The results indicate that: The level of talent management practices at Ministry of Education significantly high. The ranking of these practices from employee perspective shows that attracting and recruitment talent as the strongest influences, followed by talent selection, then retention talent, motivating and developing talent, and finally succession planning and replacement. This reflects the Ministry's interest in attracting and recruitment talented employee and then select the most talented ones, after that working to stimulate them by motivating them, developing their abilities, and planning their career path very well. The study included a number of recommendations such as: Designing modern policies and strategies to implement talent management practices in federal organizations by taking advantage of successful global experiences and practices in that area.
Keywords: إدارة المواهب -- الأداء الوظيفي -- القوى العاملة -- الإمارات